New Theoretical Model for Mass Sensitivity of Love Wave Sensors - KIEŁCZYŃSKI, Piotr; SZALEWSKI, Marek; BALCERZAK, Andrzej; WIEJA, Krzysztof (Archives of Acoustics, 2021)
In this work we analyse basic characteristics of Love wave sensors implemented in waveguide structures composed of a lossy viscoelastic surface layer deposited on a lossless elastic substrate. It has to be noted that Love wave sensors working at ultrasonic frequencies have the highest mass density sensitivity $S_σ^(v_p )$ among all known ultrasonic sensors, such as QCM, Lamb wave or Rayleigh wave sensors. In this paper we have established an exact analytical formula for the mass density sensitivity $S_σ^(v_p )$ of the Love wave sensors in the form of an explicit algebraic expression. Subsequently, using this developed analytical formula, we compared theoretically the mass density sensitivity $S_σ^(v_p )$ for various Love wave waveguide structures, such as: (1) lossy PMMA surface layer on lossless Quartz substrate and (2) lossy PMMA on lossless Diamond substrate. The performed analysis shows that the mass density sensitivity $S_σ^(v_p )$ (real and imaginary part) for a sensor with a structure PMMA on Diamond is five times higher than that of a PMMA on Quartz structure. It was found that the mass density sensitivity $S_σ^(v_p )$ for Love wave sensors increases with the increase of the ratio: bulk shear wave velocity in the substrate to bulk shear wave velocity in the surface layer.